Coping Strategies and Relationship with Burnout among Residents in Thailand - P. Kusalaruk; J. Saravithi (European Psychiatry, 2023)
Introduction Burnout is prevalent in residents and coping is one of the important modifying factors. Objectives This study aimed to investigate coping strategies, burnout, and their relationship among residents. Methods A cross-sectional descriptive study was conducted among residents from October 2019 to April 2020 in Thailand. The Brief COPE Inventory Thai version and The Maslach Burnout Inventory Thai version were used, and the associations between coping strategies and burnout were examined. Results The number of 280 residents replied the questionnaire (response rate 41.5%). The most favored copings were self-distraction and acceptance and the least common were denial and substance use. Most residents had high level of emotional exhaustion (n = 113, 40.4%) and moderate level of reduced personal accomplishment (n = 99, 35.4%). However, low degree of depersonalization was reported predominantly (n = 164, 58.6%). The coping of venting, behavioral disengagement and self-blame independently predicted emotional exhaustion and depersonalization. Behavioral disengagement was the only predictor of burnout in all dimensions, whereas positive reframing is the only strategy that had independent and protective effect against burnout in all dimensions. Table 1